Air Quality Index and the Urgency of Environmental Education in Kalimantan - Sulaeman, N. F.; Nuryadin, A.; Widyastuti, R.; Subagiyo, L. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
As one of the logical consequences of the transformation process from agricultural to industrial societies, human activities contribute some pressures to our environment, especially air quality. Kalimantan Island, as the third-largest island on Earth, expected to be the world’s lungs, transboundary massive haze problems frequently occurred on this island, especially between 2011-2015. Since the fire forest started from the Indonesia side of this island, reliable information about air quality in Kalimantan-Indonesia and environmental education’s urgency toward this result becomes essential to explore. Air Quality Index (AQI) is measured by a passive sampling method with SO2 dan NO2 as pollutants’ parameters. These two parameters are recognized as a valid measurement of air pollutants, strongly affect human health, and are understandable by ordinary citizens, especially middle school level students. AQI reached 94.27, which is categorized as a good-quality index. Among the provinces, the highest AQI was reached by East and North Kalimantan with 97.63, while South Kalimantan has the lowest with 91.41. Furthermore, the NO2 parameter contributed much larger than SO2 parameters in all provinces. AQI Kalimantan tends to increase, although South Kalimantan tended to have a lower air quality index than other provinces from year to year. This result drives comprehensive support from the education sector to build environmental understanding. From an educational perspective, this result shows the urgency of enhancing science education with air quality discussion. We suggest a possible enhancement in substance and its transformation section and the Science-Environment-Technology-Society section in Science for Junior and Senior High School. The procedure of AQI measurement and the urgency of maintaining AQI are needed to be integrated into the science curriculum.